Alcohol use and its association with suicide attempt, suicidal thoughts and non-suicidal self-harm in two successive, nationally representative English household samples - Ledden, Sarah (BJPsych Open, 2022)
Alcohol use is a risk factor for suicidal behaviour, yet the nature of the relationship is unclear. Most research on the topic is conducted in clinical populations, with few studies exploring this association across the general population.